TINGKAT PARTISIPASI, STRUKTUR PENDAPATAN, DAN KESEJAHTERAAN ANGGOTA KOPERASI TANI SURYA SEKAWAN DI DESA BANYUWANGI KECAMATAN BANYUMAS KABUPATEN PRINGSEWU - Dian Martiani; Dyah Aring Hepiana Lestari; Ktut Murniati (Lampung University, 2016)
This study aimed to determine: the participation level of the cooperative members, the effect of the participation toward the economic advantage that was received by the cooperative members, the household income structure of the cooperative members, and the prosperity level of the cooperative member. This study was conducted in Koperasi Tani Surya Sekawan Banyuwangi Village, Banyumas Subdistrict, Pringsewu Regency. The respondents were 82 farmers which were consisted of 46 rice farmers, 33 cocoa farmers, and 3 coffee farmers. The data was analyzed by descriptive analysis, linear regression analysis, and income analysis. The results showed that the participation level of members belonged to high category based on three aspects, the participation of the members in attending RAT, the participation of the members on paying off the obligation savings, and participation of the members in utilizing the service. The economic advantage which derived by the high participation members was significantly different from the low and the medium participation members. The structure of household income received by the cooperative members came from: farming income by 73.70%, the outside of farming income by 25.93%, and the economic benefits by 0.37%. The prosperity of the members based on the criteria of BPS in 2007 was belonged to the prosperous category. Key words: income, level of participation, prosperity of members